Frequent False-positive Bronchoalveolar Lavage Galactomannan Values in a Real-world Setting. (4th October 2017) - Le, Audrey; Ismail, Nour; Kubiak, David; Farmakiotis, Dimitrios; Koo, Sophia
Abstract: Background: Invasive aspergillosis (IA) is the most common invasive mold infection (IMI) and early diagnosis is critical to improving clinical outcomes. Galactomannan (GM) is a major component of the Aspergillus cell wall. BAL GM is one of the mycologic criteria for diagnosis of probable IA, but it is frequently positive in patients with Aspergillus airway colonization, and its specificity has not been well-studied. Our goal was to estimate the specificity of a positive BAL galactomannan value in a contemporary cohort of consecutive patients with BAL GM checked as part of their workup for potential IA. Methods: We reviewed clinical and microbiologic data of patients who had at least one positive BAL GM (≥0.5), at Brigham and Women's Hospital from November 2009 to March 2016. We applied EORTC/MSG IMI definitions to classify patients as having possible, probable or proven IMI, excluding BAL GM result as mycologic criterion. Results: We studied 134 patients. Median age was 58; 49% were women. 54% had hematologic malignancy (HM), 10% were solid organ (SOT) and 34% hematopoetic stem-cell transplant (HSCT) recipients. 60% received mold-active antifungal treatment. 4 patients (3%) had proven, 60 (45%) probable, 15 (11%) possible, and 55 (41%) no IMI. One had proven mucormycosis, making at least 42% of positive BAL GM results falsely positive (specificity 58%, 95% confidence interval 47–69%). 6-week mortality was 35% overall: 75% for proven, 47% probable, 33% possible, and 20% for no IMI (χ 2 for trend P = 0.008). In patients with no IMI, 6-week mortality was comparable in those who did not receive mold-active treatment (13%, 5/38) and those who did (38%, 6/16, Fischer's P = 0.07). Conclusion: In this study, at least 42% of positive BAL GM values were falsely positive, potentially exposing these patients to unnecessary antifungals. The number of 'probable' IMI cases (which, along with proven IMI are typically included in clinical trials of new antifungals) would be falsely increased by 25%, using a positive BAL GM alone to adjudicate IMI status. Accurate noninvasive tests for diagnosis of IMI are urgently needed. Disclosures: All authors: No reported disclosures.